Co-occurrence of PML-RARA gene fusion, chromosome 8 trisomy, and FLT3 ITD mutation in a young female patient with de novo acute myeloid leukemia and early death: A CARE case report. Issue 14 (April 2020) - Tripon, Florin; Crauciuc, George Andrei; Bogliş, Alina; Moldovan, Valeriu; Sándor-Kéri, Johanna; Benedek, István Jr; Trifa, Adrian Pavel; Bănescu, Claudia
Abstract: Rationale: Co-occurrence of cytogenetic and molecular abnormalities is frequently seen in patients with acute myeloid leukemia (AML). The clinical outcome and genetic abnormalities of AML may vary; therefore, genetic investigation must be complex, using several techniques, to have an appropriate characterization of the AML genome and its clinical impact. The available molecular markers can predict prognosis only partially. Acute promyelocytic leukemia subtype M3 ( AML M3) is a subtype of AML characterized by the presence of promyelocytic leukemia-retinoic acid receptor alpha ( PML-RARA ) genes fusion. Targeted treatment with all-trans-retinoic acid (ATRA) and ATRA combined with arsenic trioxide significantly improved the survival of AML M3 patients. Unknown prognostic factors could contribute to the early death of these patients. Patient Concerns: We present the case of a young female (20 years old) patient, who presented at the emergency department 5 months after giving birth to her first child, complaining of asthenia, fatigue, general musculoskeletal pain, and fever (38°C), symptoms having been present for the previous 6 days. The patient denied any chronic diseases in her medical and family history. Diagnosis: Laboratory analysis revealed severe pancytopenia. Cytogenetic and molecular analyzes revealed chromosomal abnormalities (trisomy 8), PML-RARA gene fusion, and fms-like tyrosine kinase 3 (FLT3) gene mutation. The immunophenotypic analysis was also suggestive for AML M3 according to the FAB classification. Interventions: Specific treatment was initiated for AML M3 and for secondary conditions. Molecular and cytogenetic analyzes were performed to have a more detailed characterization of the patient's genome. Outcome: Seventy-two hours after admission, she developed psychomotor agitation, confusion, coma, and convulsion. Subsequent deterioration and early death were caused by intracerebral hemorrhage with multiple localization and diffuse cerebral edema. Lessons: The presence of FLT3 internal tandem duplication (ITD) mutation may explain the rapid and progressive degradation of this AML M3 case and it may be used as a prognostic marker even when co-occuring with other markers such as PML-RARA gene fusion and trisomy 8. We consider that FLT3 ITD mutation analysis in young patients with AML should be performed as soon as possible. New strategies for patients' education, AML (or cancers in general) prevention, and treatment are needed.